Panoramic view of Boston, ca. 1960-70 - Boston Redevelopment Authority (Tufts Archival Research Center, 2005)
Elevated view looking northwest from the Custom House Tower. In the lower left corner of the photograph is the Faneuil Hall cupola and in the upper right corner is Boston Garden. The view overlooks much of Scollay Square and the West End. The southbound side of the Central Artery and Haymarket Square can be seen at the right edge of the photograph. 7 9/16 x 9 1/2 overall 8 x 10 Photographs